Porphyrin–Alkaline Earth MOFs with the Highest Adsorption Capacity for Methylene Blue. Issue 18 (22nd March 2016) - Hou, Yuxia; Sun, Junshan; Zhang, Daopeng; Qi, Dongdong; Jiang, Jianzhuang
Abstract: A series of four porphyrin–alkaline earth metal– organic frameworks [Mg(HDCPP)2 (DMF)2 ] n ⋅(H2 O)7  n (1 ), [Ca(HDCPP)2 (H2 O)2 ] n (DMF)1.5  n (2 ), [Sr(DCPP)(H2 O)(DMA)] n (3 ), and [Ba(DCPP)(H2 O)(DMA)] n (4 ) was isolated for the first time from solvothermal reaction between metal‐free 5, 15‐di(4‐ carboxyphenyl)porphyrin (H2 DCPP) and alkaline earth ions. Single‐crystal X‐ray diffraction analysis reveals the 2D and 3D supramolecular network with periodic nanosized porosity for1 /2 and3 /4, respectively. The whole series of MOFs, in particular, compounds1 and2 with intrinsic low molecular formula weight, exhibit superior adsorption performance for methylene blue (MB) with excellent capture capacity as represented by the thus far highest adsorption amount of 952 mg g −1 for2 and good selectivity, opening a new way for the potential application of the main group metal‐based MOFs. Abstract : Capture capacity : A series of four porphyrin–alkaline earth metal–organic frameworks (MOFs) with intrinsic low molecular formula weight were prepared for the first time, exhibiting the thus far highest adsorption capacity for methylene blue (MB; see figure).